Spiritual and Material Conversion in the Alchemical Work of Zosimus of Panopolis - Rinotas, Athanasios (Religions, 2021)
Zosimus of Panopolis was a Graeco-Egyptian alchemist of the 3rd century whose alchemy was imbued with both technical and Gnostic elements. In this way, the notion of conversion is met in the corpus of Zosimus in both its material and spiritual aspects. The aim of this paper is to present these two kinds of conversion by having a special focus on the role of the spirit (pneuma) in their procedures. Hence, in the first part of the study I present how pneuma is involved in the conversion of metals, while in the second I deal with the spiritual-Gnostic aspects of his alchemy, which pertain to the notion of the "divine spark." In the last part of the study, I examine the relation between pneuma and divine water in the work of Zosimus, which serves in turn as an exegetical tool for the Coptic-Gnostic source which is found in the Gospel According to Philip (61, 12b-20a).